Phylogeny and Classification of Leporidae (Mammalia, Lagomorpha) - Averianov, A.O. (Вестник зоологии, 1999)
New phylogenetic analysis of 28 genera of Neogene-Recent Leporidae based on 30 morphological characters is provided. Five new suprageneric taxa are established: Neolagomorpha, suborder n., Ochotonida, order-group taxon n., Leporida, order-group taxon n., Notolagini, triba n., Bunolagini, triba n.